The effect of Kinesio Taping on postural control in subjects with non-specific chronic low back pain - Abbasi, Soheila; Rojhani-Shirazi, Zahra; Shokri, Esmaeil; García-Muro San José, Francisco (Journal of bodywork and movement therapies, 2018)
The aim of this study was to investigate the possible alterations in postural control during upright standing in subjects with non-specific chronic low back pain and the effect of Kinesio taping on the postural control. Twenty subjects with non-specific chronic low back pain and twenty healthy subjects participated in this study. The center of pressure excursion was evaluated before the intervention for both groups, and immediately after intervention for the low back pain group. Independent sample t-test, Mann-Whitney test and repeated measure ANOVA were used for the statistical analysis of the data. There were significant differences in the center of pressure excursion between the low back pain group versus the healthy group. The results of the ANOVA demonstrated a statistically significant difference in the mean COP displacement and velocity before Kinesio Taping, immediately after, and 24 h after in the low back pain group. There are poor postural control mechanisms in subjects with non-specific chronic low back pain. Kinesio taping seems to change postural control immediately and have lasting effects until the day after.